DNA sequence elements located immediately upstream of the -10 hexamer in Escherichia coli promoters: a systematic study - Tom Burr; John C. Mitchell; Annie Kolb; Steve Minchin; Stephen Busby (2000)
We have made a systematic study of how the activity of an Escherichia coli promoter is affected by the base sequence immediately upstream of the –10 hexamer. Starting with an activator-independent promoter, with a 17 bp spacing between the –10 and –35 hexamer elements, we constructed derivatives with all possible combinations of bases at positions –15 and –14. Promoter activity is greatest when the ‘non-template’ strand carries T and G at positions –15 and –14, respectively. Promoter activity can be further enhanced by a second T and G at positions –17 and –16, respectively, immediately upstream of the first ‘TG motif’. Our results show that the base sequence of the DNA segment upstream of the –10 hexamer can make a significant contribution to promoter strength. Using published collections of characterised E.coli promoters, we have studied the frequency of occurrence of ‘TG motifs’ upstream of the promoters’ –10 elements. We conclude that correctly placed ‘TG motifs’ are found at over 20% of E.coli promoters.